European universities during the crisis: A public policy perspective, with a brief excursion to the US - Jo Ritzen (Institute for the Study of Labor (IZA), 2015)
The crisis slowed down the implementation of the Lisbon Strategy (for the EU to become the most competitive region in the world). The crisis has aggravated the divergence between the North West of Europe and Southern Europe in labor productivity imparted by the knowledge economy. At the same time, equality of opportunity for participation in higher education seems to have been well-preserved in the EU Member States. This is in contrast to the US with its substantial higher private costs for university education. The relative stagnations in university education and research during the crisis is similar in Europe as in the US. Asian countries may - as a result - have improved their position in innovation. The room for maneuver of Governments of EU Member States to deal with universities (as with other public expenditures) was severely limited by the agreed upon maximum levels of the budget deficit and Government debt. Political institutions appear to determine the "code" for higher education expenditures. The quality of the minister responsible for higher education and the level of "trust" in the country may also the room for maneuver in setting university policy.
Keywords: H2; H6; I22; I23; I24; I28; O31; O38; O43; O51; O52; 330; economic crisis; university policy; university funding; equity; innovation; labor productivity; trust